(untitled) - Reis Pinheiro, Carlos Andre (New Jersey, 2014)
Heuristics in Analytics contains the information analysts need to improve accuracy, and ultimately, predictive, and descriptive power.
Keywords: Management,Decision making,Business planning,Quản lý,Ra quyết định,Kế hoạch kinh doanh; Statistical methods,Statistical methods,Statistical methods,Phương pháp thống kê,Phương pháp thống kê,Phương pháp thống kê